Chemical comparison and acute toxicity of water accommodated fraction (WAF) of source and field collected Macondo oils from the Deepwater Horizon spill. Issue 1 (15th February 2015) - Faksness, Liv-Guri; Altin, Dag; Nordtug, Trond; Daling, Per S.; Hansen, Bjørn Henrik
Highlights: Chemistry and acute toxicity in WAFs from source and field oils from DWH. WAFs prepared to evaluate impact of natural weathering on chemistry and toxicity. Acute toxicity tests using S. costatum (algae) and A. tonsa (copepod) performed. Potential for toxicity higher in WAFs from non-weathered than field-weathered oils. Abstract: Two Source oils and five field collected oil residues from the Deepwater Horizon incident were chemically characterized. Water accommodated fractions (WAFs) of the Source oils and two of the field-weathered oils were prepared to evaluate the impact of natural weathering on the chemical composition and the acute toxicity of the WAFs. Toxicity test species representing different tropic levels were used (the primary producer Skeletonema costatum (algae) and the herbivorous copepod Acartia tonsa ). The results suggest that the potential for acute toxicity is higher in WAFs from non-weathered oils than WAFs from the field weathered oils. The Source oils contained a large fraction of soluble and bioavailable components (such as BTEX (benzene, toluene, ethyl benzene, xylenes) and naphthalene), whereas in the surface collected oils these components were depleted by dissolution into the water column as the oil rose to the surface and by evaporative loss after reaching the sea surface.